Adopting Consensus Terms for Testing in Precision Medicine. (2021) - Martin, Nikki A.; Tepper, Joel E.; Giri, Veda N.; Stinchcombe, Thomas E.; Cheng, Heather H.; Javle, Milind M.; Konnick, Eric Q.
Abstract : PURPOSE: Despite the well-understood benefits of biomarker and genetic testing in precision medicine, uptake remains low, particularly for patients with low socioeconomic status and minority ethnic backgrounds. Patients report having limited familiarity with testing terminology and may not be able to accurately explain testing's role in treatment decisions. Patient confusion and lack of understanding is exacerbated by a multiplicity of overlapping terms used in communicating about testing. A LUNGevity Foundation–led working group composed of five professional societies, 23 patient advocacy groups, and 19 industry members assessed and recommended specific terms for communicating with patients on testing for tumor characteristics and germline mutations. METHODS: Members completed a precision oncology testing framework analysis (biomarkers, germline variants, testing modalities, biospecimen, and commonly used testing terms) for nine solid tumors and blood cancers. The evaluation was segmented into terms that distinguish between somatic and germline testing. Additional data were captured in a comprehensive survey (1, 650 respondents) led by FORCE (Facing Our Risk of Cancer Empowered) on patient preferences on germline testing terms. RESULTS: Thirty-three terms were noted in patient education related to biomarker, genetic, and genomic testing. Biomarker testing was selected as the preferred term for testing for somatic (acquired) alterations and other biomarkers. Genetic testing for an inherited mutation and genetic testing for inherited cancer risk were selected as the preferred terms for testing for germline variants. CONCLUSION: Democratizing comprehension about precision oncology testing through intentional use of plain language and common umbrella terminology by oncology health care providers and others in the oncology ecosystem may help improve understanding and communication, and facilitate shared decision making about the role of appropriate testing in treatment decisions and other aspects of oncology care.